The EU's enlargement policy: Ways out of the impasse - Barbara Lippert (Stiftung Wissenschaft und Politik (SWP), 2009)
The enlargement policy of the European Union (EU) has reached an impasse both politically and conceptually. The accession of Cyprus, Bulgaria and Romania is now considered a warning against the overhasty admission of new members. Accession negotiations with Croatia and Turkey have been dragging on for four years - and the end is still not in sight. The development of an Eastern Partnership with the six post-Soviet states will give the EU a breathing-space and postpone any further promises of accession. Even applications which were expected, such as Montenegro's and Albania's or most recently Iceland's, met with annoyance or a merely businesslike reaction from member states. Few of them now still see these accession wishes as proof of the vitality and attractiveness of the EU. Enlargement, once regarded by member states as part of the active advancement of the EU, has reached its limits. Notwithstanding this, new applications set the negotiation machinery in motion as if automatically. This is one of the causes of the malaise of enlargement policy which needs to be fundamentally rethought, especially in view of possible new interactive structures such as an 'E3' consisting of the EU, Turkey and Russia
Keywords: 320